ACETOSAL, BUAH MENGKUDU (MORINDA CITRIFOLIA L.) DAN WAKTU PERDARAHAN - I Wayan Putu Sutirta Yasa; Ketut Widyani Astuti; I Gusti Made Aman (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
Research regardless the effect of noni fruit for increasing bleeding time have already been carried out widely. The similar activity ofnoni fruit extract and acetosal can be concerned that the fruit extract has a potential activity for prolonged bleeding time. This study aimsto know the present of prolonged of bleeding time as a results of intake of combination of noni fruit extract with acetosal on mice. Thisresearch was carried out at Unit Binatang Percobaan, Departemen Farmakologi Universitas Udayana. This is an experimental study withpre and post-test control group design. Subject was compromised of 3 groups of mice and each group contain of 7 mice. The first groupwas treated with a dose of 40 mg/kg bw acetosal, the second group treated with a dose of 100 mg/kg bw ethanol noni fruit extract, andthe third group treated with combination of 40 mg/kg bw acetosal and 100 mg/kg bw ethanol extract of noni fruit. All groups werefed once per day for a week. Bleeding time was determined on the basis of tail bleeding method. This study results that the first groupexperience bleeding time increased from 61.42±9.43 second to 160.71±19.77 second. Increase bleeding time of the second group is from59.14±7.12 to 138.14±59.91 second. For the third group, the bleeding time increases from 65.00±7.91 to 213.00±20.92 second.One Way ANOVA analysis indicates that there is a significant different among these three groups after treatment p = 0.006 (p<0.05).Bleeding time of the third group which was treated with combination of noni fruit and acetosal results in the highest increase compareto the other two groups. In conclusions, combination of noni fruit and acetosal treatment results in increase of bleeding time on mice.